STRATEGI PEMERINTAH DESA DALAM PENANGGULANGAN STUNTING - Alfadinda, Tarissa Putri; Lailul Mursyidah (Sawala : Jurnal Administrasi Negara, 2024)
This research aims to evaluate the village government's strategy in dealing with cases of stunting risk. The technique used is descriptive qualitative, which is divided into primary data and secondary data. The focus of this research is the village government's strategy to overcome cases of stunting risk through an accelerated stunting reduction program. The results of this research show that the village government's strategy in overcoming stunting has not been optimal, this is due to the lack of formation of a Stunting Reduction Acceleration Team (TPPS) whose task is to evaluate the implementation of accelerated stunting reduction at the village level, lack of tools to monitor the growth and development of toddlers, lack of socialization about stunting to village communities. With the village government's strategy of carrying out stunting prevention activities by providing a budget for providing additional food (PMT), increasing the provision of clean water and sanitation and holding classes for pregnant women